Productivity and export market participation: Evidence from Colombia - Camila Casus; Federico J. Díez; Alejandra González; Stefany Moreno (Federal Reserve Bank of Boston, 2014)
Using evidence from Colombia, the authors study the relationship between firms' productivity and their export market participation decisions. Understanding the link between these two variables is critical for the study and design of policies aimed at achieving high and sustainable economic growth in the long run.
Keywords: F14; L22; L60; 330; productivity; exporters; productivity premium; openness